Cross-sensory correspondences in language: Vowel sounds can symbolise the felt heaviness of objects - Walker, Peter *; Regina, Parameswaren C (American Psychological Association, 2019)
In sound symbolism, a word's sound induces expectations about the nature of a salient aspect of the word's referent. Walker (2016a) proposed that cross-sensory correspondences can be the source of these expectations and the present study assessed three implications flowing from this proposal. First, sound symbolism will embrace a wide range of referent features, including heaviness. Second, any feature of a word's sound able to symbolise one aspect of the word's referent will also be able to symbolise corresponding aspects of the referent (e.g., a sound feature symbolising visual pointiness will also symbolise lightness in weight). Third, sound symbolism will be independent of the sensory modality through which a word's referent is encoded (e.g., whether heaviness is felt or seen). Adults judged which of two contrasting novel words was most appropriate as a name for the heavier or lighter of two otherwise identical hidden novel objects they were holding in their hands. The alternative words contrasted in their vowels and/or consonants, one or both of which were known to symbolise visual pointiness. Though the plosive or continuant nature of the consonants did not influence the judged appropriateness of a word to symbolise the heaviness of its referent, back/open vowels, compared to front/close vowels, were judged to symbolise felt heaviness. The symbolic potential of back/open vowels to represent felt heaviness, predicted on the basis of their symbolism of visual roundedness, supports the proposal that cross-sensory correspondences contribute to sound symbolism